Words vs. Deeds : What Really Matters? - Qureshi, Mahvash; Ghosh, Atish; Tsangarides, Charalambos (Washington, D.C. : International Monetary Fund, 2011)
This paper revisits the link between the nominal exchange rate regime and inflation, based on a sample of 145 emerging market and developing countries (EMDCs) over the period 1980-2010. We contend that, just as a de jure peg that is not backed by a de facto peg will have little value, de facto pegs that lack the corresponding de jure will likewise reap few of the low inflation benefits associated with pegging the exchange rate. To test our hypothesis, we exploit a novel dataset of both de jure and de facto exchange rate regime classifications. We find that pegged exchange rates are associated with significantly lower inflation in EMDCs than flexible exchange rates, and that this effect is much stronger for de facto pegs that are matched by de jure pegs than for those that are not. When it comes to anchoring expectations and delivering low inflation, therefore, both deeds and words matter.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet